2020
DOI: 10.1051/e3sconf/202020206027
|View full text |Cite
|
Sign up to set email alerts
|

Tidal flooding and coastal adaptation responses in Pekalongan City

Abstract: Over the past 10 years, the coastal region of Pekalongan City has experienced the phenomenon of tidal flooding and has almost submerged coastal areas almost daily. At present, tidal floods have submerged 51% of the total area of Pekalongan City with a maximum inundation height of 1.1 meters. As a result, there has been damage to the economic, social, and physical (infrastructure). Adaptation response from all parties involved is needed to reduce negative impacts. The writing of this manuscript aims to find out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 2 publications
0
3
0
1
Order By: Relevance
“…Pekalongan City, Central Java, is an urban area that often experiences floods and tidal disasters. The research predicted the increase of flood in this area could attain 36 cm in 2025 and 132 cm in 2050 [2], [3]. The latest study also identified that tidal flooding had enlarged yearly.…”
Section: Introductionmentioning
confidence: 82%
See 1 more Smart Citation
“…Pekalongan City, Central Java, is an urban area that often experiences floods and tidal disasters. The research predicted the increase of flood in this area could attain 36 cm in 2025 and 132 cm in 2050 [2], [3]. The latest study also identified that tidal flooding had enlarged yearly.…”
Section: Introductionmentioning
confidence: 82%
“…The latest study also identified that tidal flooding had enlarged yearly. In 2020 alone, the tidal flood coverage area was 783.99 hectares [4], while other research asserted that tidal floods had affected 50% of Pekalongan city [3].…”
Section: Introductionmentioning
confidence: 97%
“…The circulation pattern of the study area is governed by the impacts of surface currents driven by monsoon winds and the tidal effects and circulation masses as it flows (Pratama, 2019). The tides along the coast of Pekalongan waters are predominantly mixed tide prevailing diurnal tides (Maharlika et al, 2020). Tidal data obtained from the Geospatial Information Agency (BIG), 2022 iPASOET | Sea Level Monitoring (big.go.id), which is then processed using the admiralty method.…”
Section: Methodsmentioning
confidence: 99%
“…On the contrary, Cihara sub-district was the least number of population and the lowest level of vulnerability to the tsunami disaster with a population of 31,826 -33,174 people. The high population density illustrates the high probability of loss of life and property hence threatening the community's survival [18]. Very high population densities will be more vulnerable to tsunamis than areas with lower densities because they have a high potential for victims when a tsunami arrives [19].…”
Section: Potential Population Exposed To Tsunamimentioning
confidence: 99%